Modernisasi Media Pembelajaran Pendidikan Agama Islam dalam Menumbuhkan Karakter Religius Siswa di SD IT Al-Washliyah Hamparan Perak - Syafrida Rahmidayani Barus; Mhd. Habibu Rahman; Danny Abrianto (Islam & Contemporary Issues, 2025)
This study examines the modernization of Islamic Religious Education (PAI) learning materials in fostering students’ religious character at SD IT Al-Washliyah Hamparan Perak. The research aims to analyze the forms of media modernization applied in PAI instruction, identify supporting and inhibiting factors, and assess its implications for students’ religious character development. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation involving PAI teachers and school administrators. The findings indicate that teachers integrate various digital media, including interactive applications, animated learning videos, and instructional social media platforms, to enhance students’ learning engagement and comprehension. The use of digital media not only increases students’ interest in PAI lessons but also facilitates the internalization of religious values such as integrity, responsibility, and self-discipline. Supporting factors include teachers’ pedagogical competence and strong institutional support, while constraints mainly involve limited technological facilities and unequal levels of teachers’ digital literacy. This study contributes by offering a practical model of PAI learning media modernization and highlighting its pedagogical implications for character education in elementary schools. Overall, the modernization of PAI learning materials is shown to be effective in creating meaningful learning experiences that support the development of students’ religious character.